2020
DOI: 10.5194/egusphere-egu2020-8686
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transport under advective trapping

Abstract: <p>Advective trapping occurs when solutes enter a low velocity zone in the porous medium. Current multirate mass transfer (MRMT) models consider slow advection and diffusion but do not separate these processes, which makes parameterization difficult. Here we investigate the impact of advective trapping on transport in media consisting of isolated low permeability inclusions. Breakthrough curves show that effective transport changes from a streamtube model to genuine MRMT as the degree of disorder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…More saturated porous media exhibit a less heterogeneous velocity field (Triadis et al 2019;Velásquez-Parra et al 2021) and therefore less deformation. This is also manifest in the enhanced spreading of the interface (Boon et al 2017;Comolli et al 2019;Hidalgo et al 2021) shown in Fig. 6.…”
Section: Dispersion Of the Mixing Interfacementioning
confidence: 82%
“…More saturated porous media exhibit a less heterogeneous velocity field (Triadis et al 2019;Velásquez-Parra et al 2021) and therefore less deformation. This is also manifest in the enhanced spreading of the interface (Boon et al 2017;Comolli et al 2019;Hidalgo et al 2021) shown in Fig. 6.…”
Section: Dispersion Of the Mixing Interfacementioning
confidence: 82%